The Modernization of Islamic Educational Institutions: Answering Educational Challenges - Supriyanto Supriyanto; Fantika Febry Puspitasari; Agus Sriyanto (Universitas Muhammadiyah Malang, 2020)
Education is the life of civilization, meaning that only with education will an ideal civilization be realized. The ideal education will be challenging to realize while the management structured by the Principal as the supreme leader in the school is not of quality. Therefore, between quality education and quality education management must be an integral entity. The two components work hand in hand to produce qualified graduates. The head of SD Muhammadiyah 3 Assalam and SMK Muhammadiyah 1 Malang managed to modernize their school's management of his school so that the quality of graduates had high competitiveness. The management was named School Management,